Pemanfaatan Terapi Musik untuk Meningkatkan Status Kesadaran Pasien Trauma Kepala Berat - Asrin; Mardiyono; Saryono (Jurusan Keperawatan FIKES UNSOED, 2007)
As a therapeutic intervention music has a positive chance for rehabilitation of severe traumatic brain injury patients. However, many studies mention that the uses of music in health fields are still uncertainly result. This research was conducted to prove the uses of music therapy for increasing the consciousness level of severe traumatic brain injury patients and to know the physiology and psychosocial responses of patients during therapy. This study utilized a quasi-experimental method with non randomized pretest-posttest control group design. The respondents were severe traumatic brain injury patients on Cempaka and ICU wards of Prof. Dr. Margono Soekarjo Hospital Purwokerto who were chosen based on inclusion and exclusion criteria. The total of respondents was 20 respondents who were divided into 10 of respondents as treatment group and 10 respondents as control group. The analysis of data was conducted by using one sample t test and the descriptive analysis also was utilized. The study result shows that the music therapy is useful for increasing the consciousness level of severe traumatic brain injury patients (t test value = 11,781 > t table value; CI = 95%, and p value = 0.000). From descriptive data can be concluded that the response of psychology and psychosocial patients of severe traumatic brain injury in treatment group was positively significant for arousing and raising the excitability of movement performance. The result indicated that the music therapy is useful for increasing the consciousness level of severe traumatic brain injury patients and familiar music also can enhance positive response of psychology and psychosocial patients’ response.